Pengembangan Sediaan Losio Ekstrak Buah Naga Putih - Husni, Patihul; Budianto, Muhamad Oke; Baitariza, Ardian; Eryani, Mikhania Christiningtyas; Febryanto, Hery Diar; Januarti, Melinda (Universitas Bhakti Kencana, 2025)
White dragon fruit (Hylocereus undatus) is a tropical fruit from a type of cactus plant that contains various powerful antioxidants. The purpose of this study was to obtain the best lotion formula containing extract of white dragon fruit based on physical evaluation. Three lotion formulas (F1, F2, F3) containing 7,5% white dragon fruit extract were prepared in this study. Physical assessment of the lotion preparation included organoleptic tests, homogeneity, pH determination, and viscosity evaluation. The results showed that the preparation was in the form of a liquid and homogeneous lotion with a white color and a rose odor. The pH of the preparation was around 5.2-6.5 with a viscosity between 1200-1800 cps. F3 is the best lotion formula based on physical evaluation during four weeks of storage with a composition of 7.5% white dragon fruit extract, 1% glycerin, 0.05% triethanolamine, 3% liquid paraffin, 0,3% methyl paraben, 2% dimethicone, 2% stearyl alcohol, 1.5% glycerol monostearate, 3% virgin coconut oil, 0.1% disodium edetate, 3% cetyl alcohol, 0.2% titanium dioxide, parfum qs, and aquadest ad 100%.